THE LEVEL OF FAMILY CONFLICTS AND THEIR RELATIONSHIP TO PARENTAL ABSENTEEISM AMONG A SAMPLE OF MIDDLE ADOLESCENT STUDENTS - Aljawarneh, Ahmad Y (PEOPLE: International Journal of Social Sciences, 2019)
The study aimed at exploring the connection between parental absenteeism and family conflict among a sample of middle adolescent students. In addition, the study sought to identify the levels of family conflict and parental relations among the sample and the link between parental absenteeism and family conflict. The combined effect of parental absenteeism and gender on them. The sample was composed of 446 students, 240 (53.8%) male and 206 (46.2%) female students. The descriptive research method was adopted in this study. The instruments used in this scale were built by the researcher to measure the levels of family conflicts. Results from the study revealed that individuals in the sample achieved an average degree on the scales of family conflicts. Significant statistical differences attributed to gender were found on the scale of family conflicts in favor of females. Moreover, significant statistical differences were found relating to parental absenteeism on the scale of family conflicts in favor of mother absenteeism. An effect relating to the interaction between gender and parental absenteeism was found on the scale of family conflicts except for the dimensions: Psychological problems.